Influence of Flexible Classroom Seating on the Wellbeing and Mental Health of Upper Elementary School Students: A Gender Analysis - Bluteau, Jonathan; Aubenas, Solène; Dufour, France (Frontiers in Psychology, 2022)
While traditional seating (also known as fixed seating or fixed classroom) remains the preferred classroom seating arrangement for teachers, a new type of seating arrangement is becoming more common in schools: the flexible classroom (also known as flexible seating). The purpose of this type of arrangement is to meet the needs of students by providing a wide variety of furniture and workspaces, to put students at the center of learning, and to allow them to make choices based on their preferences and the objectives of the task at hand. This study aimed to examine the influence of flexible seating on the wellbeing and mental health of elementary school students. This article presents the results of exploratory research conducted in Quebec among Grade 5 and 6 students comparing the wellbeing and mental health of students in fixed and flexible classrooms. The study was conducted with 107 students in three Grade 5 and 6 flexible classrooms (n = 51) and three Grade 5 and 6 fixed classrooms (n = 56). It is based on a quasi-experimental, quantitative design with post-test only and a control group. The groups were matched based on natural conditions (i.e., from a convenience sample). Furthermore, the study included a gender-differentiated analysis for each group. The results showed that flexible classroom seating had a positive influence on the girls’ wellbeing and mental health. In contrast, for the boys, fixed classroom seating was most conducive to their wellbeing and mental health. However, our study has some limitations that are discussed in the article.